TRANSFORMATION OF PPDB TOWARDS DIGITALIZATION: CONVENIENCE AND CHALLENGES IN THE ONLINE REGISTRATION SYSTEM AT https://smkn1barru.sch.id/ppdb.php - Pratiwi, Dian; A.Aminah (P3M Stia Al Gazali Barru and Meraja media, 2024)
[Full Paper] to pdf Copyright (c) 2024 Meraja journal